High-Titer Rheumatoid Factor is Associated with Worse Clinical Outcomes and Higher Needs for Advanced Therapies in Rheumatoid Arthritis Under Real-Life Conditions - Victor Davi R. S. Oliveira; Ana Paula M. G. Reis; Claiton V. Brenol; Ivânio A. Pereira; Karina R. Bonfiglioli; Letícia R. Pereira; Manoel B. Bértolo; Maria de Fátima L. C. Sauma; Maria Fernanda B. R. Guimarães; Paulo Louzada-Júnior; Rina D. N. Giorgi; Sebastião C. Radominski; et al. (Rheumatology and Therapy)
Abstract Introduction Rheumatoid factor (RF) plays an important role in rheumatoid arthritis (RA) pathophysiology, yet the differential effects of varying RF titers remain understudied. We evaluated associations between different RF titers and clinical outcomes in long-standing RA. Methods This multicenter, cross-sectional study included adults meeting ACR/EULAR (2010) criteria for RA. Circulating RF titers and clinical-epidemiological characteristics were evaluated. Bivariate (Student’s t and chi-squared tests) tests and multiple logistic and linear regression analyses were conducted. Results We included 1097 participants; 78.7% had positive RF, with high titers (≥ 3 × the upper limit of normality) in 56.2%. Negative vs. low-positive RF groups performed similarly concerning all clinical outcomes, being subsequently aggregated as "non-high" RF group. High RF titers (compared to "non-high") were associated with tobacco use (odds ratio, OR [95% confidence interval, CI]: 2.04 [1.35, 3.08]; p < 0.001), multiraciality (OR [95% CI] 1.31 [1.03, 1.67]; p = 0.028, compared to White race), and higher body mass index (mean difference [95% CI] 0.69 [0.05, 1.33] kg/m2; p = 0.033). In multivariate analyses, high-titer RF was independently associated with higher disease activity (Clinical Disease Activity Index, CDAI: β = 2.44 [0.89, 3.99], p = 0.002), worse functional capacity (Health Assessment Questionnaire Disability Index, HAQ-DI: β = 0.112 [0.018, 0.205], p = 0.020); extra-articular manifestations (OR 1.48 [1.09, 2.00], p = 0.011); increased corticosteroid (OR 1.53 [1.19, 1.96], p = 0.001) and biological disease-modifying antirheumatic drugs (bDMARD) use (OR 1.41 [1.08, 1.84], p = 0.011). Conclusions High RF titers in long-standing RA were associated with worse disease activity, lower physical functionality, increased extra-articular manifestations, and higher usage of corticosteroids and bDMARDs. Comparing high vs. non-high RF titers (rather than positive vs. negative RF) seems more useful for evaluating the clinical effects of RF in RA. This approach should be considered in future studies of RF.